P96 Repeat Administration of GL67A/pGM169 is Feasible, Safe, and Produces Endogenous Levels of CFTR Expression After 12 Doses. (19th November 2012) - Alton, EWFW; Boyd, AC; Cheng, SH; Davies, J; Davies, LA; Dayan, A; Gill, DR; Griesenbach, U; Higgins, T; Hyde, SC; Innes, A; McLachlan, G; et al.
Abstract : For gene therapy to improve lung function in CF subjects, repeated administration of the gene transfer agent over the lifetime of a patient will be necessary. This requirement limits the usefulness of adenoviral and adeno-associated viral vectors (both commonly used in CF gene therapy in the past), because these viral vectors induce adaptive immune responses which render repeat dosing ineffective. Thus, for CF gene therapy non-viral vectors are currently the only viable option. We have, therefore, undertaken an extensive pre-clinical research programme to select the most efficient non-viral vector for a Multi-dose CF trial. The cationic lipid formulation GL67A was ultimately chosen and combined with a CpG-free CFTR plasmid (pGM169). We recently completed a single-dose Phase 2a clinical safety and molecular efficacy study, which demonstrated proof-of principle for long lasting (several weeks) correction of the CF-specific chloride transport defect, but also indicated that the toxicity-efficacy window is comparatively narrow. To support the trial, we undertook a murine repeat dose (12 doses over 6 months) efficacy, biodistribution and toxicology study. We show that (a) repeated lung administration of pGM169/GL67A is safe and feasible using a clinically relevant nebuliser, (b) achieves reproducible, dose-dependent and persistent gene expression (>140 days after each dose) and importantly (c) allows for a cumulative treatment effect (as measured by levels of vector-specific mRNA) particularly when working in a clinically relevant dosing range (dose 1: 0.8% vector-specific/endogenous mCftr (range 0–1.8), dose 12: 74% vector-specific/endogenous mCftr (range 31.6–204). The results of this repeat dosing study in the mouse therefore (1) demonstrate that endogenous levels of CFTR mRNA can be achieved by exogenously applied gene therapy (cumulative effect), and (2) affirm the UK CF Gene Therapy Consortium's strategy of repeat dosing.